Antagonistic potentiality of bioagents against wilt of cumin (Cuminum cyminum) caused by Fusarium oxysporum f. sp. cumini - KUMAR, SURESH; GANGOPADHYAY, GANGOPADHYAY; GODARA, S L (The Indian Journal of Agricultural Sciences, 2016)
Efficacy of various fungal and bacterial antagonists isolated from cumin rhizosphere were evaluated against wilt of cumin (Cuminum cyminum L.) caused by Fusarium oxysporum f. sp. cumini was observed under laboratory and green house conditions. The disease control potentiality of 15 selected antagonists used as seed treatment and soil application against Fusarium wilt was also studied under field conditions. The fungal antagonists Trichoderma viride (SIF-120), T. pseudokoningii (Tp-50), T. harzianum (Th-1) and C. sitophila (SIF-444) significantly (Pâ‰¤0.05) inhibited the mycelial growth of F. oxysporum f. sp. cumini. The bacterial antagonists Pseudomonas fluorescens (Pf-5), P. fluorescens (Pfg-33), Bacillus subtilis (Bs-10) and B. subtilis (Bs-77) were found highly inhibitory to the pathogen under laboratory conditions. The seed treatment and soil application with T. viride (SIF-120), P. fluorescens (Pf-5) and T. pseudokoningii (Tp-50) provided effective disease control under green house conditions. T. viride (SIF-120) and P. fluorescens (Pf-5) bioagents used as seed treatment and soil application provided maximum control (70.03 and 67.14%, respectively), of cumin wilt under field conditions. Maximum root length, shoot length and dry weight were observed in response to T. viride (SIF-120) closely followed by P. fluorescens (Pf-5) treatments. Highest cumin seed yield (6.05 q/ha) was recorded in T. viride (SIF-120) treatment followed by P. fluorescens (Pf-5) and T. pseudokoningii (Tp-50) treatments.